IS THE CARBON TAX A HARMFUL TAX? EVIDENCE FROM INDONESIA - Fidiana, Fidiana; Dwi Retnani, Endang (Economic Review: Journal of Economics and Business, 2025)
The uncertainty about the timing of the implementation of carbon tax regulations has drawn significant public attention. Does this attention represent public support? This research attempts to explore the public perspective on the government’s delay in implementing carbon tax. This study involves key societal stakeholders relatively closely connected to the carbon tax issue, including tax authorities, tax advisors, academics, as well as certain taxpayers.. Since there is no “one-size-fits-all“ carbon tax, developing nations should tailor their designs to the many economic, political, and administrative environments in which they operate. There are concerns about how carbon tax, as a form of green taxation, can affect productivity, equality, and competitiveness. However, this paper argues that these challenges can be resolved. For instance, output-based rebates can offer protection even though ETR (Environmental Tax Reform) may increase the productivity and competitiveness of impacted enterprises. This research found that governments often postpone carbon tax implementation due to low confidence in tax authorities. Even if the government actually does allocate a carbon tax to protect the environment, the public may remain sceptical. Tax authorities are responsible for implementing commitment tools to assure the public that carbon tax revenues will be used as promised. The government needs to reconsider existing carbon taxes to prevent overlap even when their goals align.